Health Care Professionals’ Perception of Contraindications for Physical Activity During Cancer Treatment - Tsiouris, Angeliki; Ungar, Nadine; Haussmann, Alexander; Sieverding, Monika; Steindorf, Karen; Wiskemann, Joachim (Frontiers in Oncology, 2018)
Introduction Suggested medical contraindications for physical activity (PA) during cancer therapy might have an influence on PA recommendation behavior of Health Care Professionals (HCP). The purpose of the present study was to examine perceptions of physicians and oncology nurses (ON) toward specific medical conditions as contraindications for PA during cancer treatment. Materials and methods A total of 539 physicians and 386 ON were enrolled in this cross-sectional survey. HCP judged 13 medical conditions as to whether they are contraindications for PA during cancer treatment. Answering format was “no contraindication”/“potentially a contraindication”/“yes, a contraindication.” Results χ2 analyses revealed significant differences between general practitioners, specialized physicians, and ON in their perception of 10 medical conditions. Approximately half of the medical conditions were answered cautiously, showing high numbers on the response option potentially (36–72%). Moreover, physicians’ ratings differed significantly depending on their practical experience with particular medical conditions. Those being familiar with a specific medical condition was more permissive to PA during treatment, with effect sizes (Cramer’s V) ranging from 0.13 to 0.27. Conclusion Results indicate high cautiousness among HCP in judging medical conditions and their impact on PA during cancer treatment. However, group comparisons show that familiarity and clinical experience with potential contraindications facilitate a confident handling of safety issues, which at best leads to higher levels of PA recommendations during cancer treatment.